Subtyping Gambling Acitivities: Case of Korca City, Albania - Shahini, Besa; PhD candidate: Emil FRASHERI (European Journal of Multidisciplinary Studies, 2016)
Gambling research has grown dramatically over the past 2-3 decades, however a lack of consensus regarding the risk factors and gambling etiology related to youth problem gambling still remain. So a better understanding of the nature of youth problem gambling could help us to clarify the etiology of gambling problems. Understanding gambling subtypes is necessary to improve our understanding of the etiology of problem gambling. The prediction of problem gambling is related with the participation in gambling activities. It is necessary to obtain a structure of gambling activities, in order to better understand gambling related problems and to treat problems in a more specified manner. The aim of the study was to determine the appropriate structure of gambling activities using factor analysis in a confirmatory framework. Students are a particularly interesting population in which to study gambling. The research utilized a cross-sectional design and self-report questionnaires. The study concludes that the two-factor solution better represents the chance-and skill-based gambling activities. The first factor is most strongly associated with chance-based activities (lottery, bingo, scratch cards). The second factor is most strongly associated with activities that require some degree of skill (poker, roulette, sport bet, racing, etc. ).
Keywords: Gambling, Latent classes, Probability